Remote learning in the time of post COVID-19: interactive PDPR system for primary school via visual basic programming / Samsiah Abdul Razak ... [et al.] - Abdul Razak, Samsiah; Abdullah, Ini Imaina; Mohamad Radzi, Nur Insyirah; Omar, Aslina (Universiti Teknologi MARA, Perak, 2023)
Abstract between 150-250 words only. It has been more than a year since the implementation of movement order control (MCO) on March 18, 2020, in Malaysia. In March 2020, PdPR 1.0 was initially implemented. Through this e-learning distance education, technology plays a key role in designing online learning environments that meaningfully engage students. To learn online via these platforms, a student would need to have access to the platform and guidance from parents. Some parents have faced various challenges since the introduction of PdPR. they cannot afford to provide sufficient gadgets for their children, and most of the students faced internet problem and did not have the knowledge to use technology and find it difficult to participate in online learning. Teachers are also impacted by this problem when students learn online.The system development of this project is using a waterfall model that consists of requirements, design, and development phases. Hence, to create an application that would aid teachers and students in the process of online teaching and learning, this study introduces the application system using Visual Basic programming 2010 known as "VB," and it is designed to make software creation quick and simple while still being strong enough to construct complex programs. This study only focuses on the problem faced by primary school students (Year 4, 5, and 6) and on the curriculum's emphasis on four core subjects: Bahasa Melayu, English, Mathematics, and Sciences. Hopefully, using this application will give some excitement to teachers and students for their online teaching and learning.